2020
DOI: 10.3389/fgene.2020.00507
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of the Role of Previously Reported Risk Factors in the Age at Menopause Using Mendelian Randomization

Abstract: Objective: Menopause at a young age is associated with many health problems in women, including osteoporosis, depressive symptoms, coronary disease, and stroke. Many traditional observational studies have reported some potential risk factors for early menopause but have drawn different conclusions. This inconsistency can be attributed mainly to unmodified confounding factors. Identifying the factors causally associated with age at menopause is important for early intervention in women with abnormal menopause t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 66 publications
4
12
0
Order By: Relevance
“…We substantiate the genetic correlation between reproductive factors shown in previous studies, while showing additional correlations that have not been previously investigated. (57,58) Our study supports evidence for a positive causal link between AAM and age at menopause, (11)(12)(13)(14)(15)(16)59,60) and opposes previous studies that have shown the inverse association, (17,18) or no association. (19)(20)(21)(22)(23)(24) Furthermore our findings support one study that found little evidence for an association between AAM and parity.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We substantiate the genetic correlation between reproductive factors shown in previous studies, while showing additional correlations that have not been previously investigated. (57,58) Our study supports evidence for a positive causal link between AAM and age at menopause, (11)(12)(13)(14)(15)(16)59,60) and opposes previous studies that have shown the inverse association, (17,18) or no association. (19)(20)(21)(22)(23)(24) Furthermore our findings support one study that found little evidence for an association between AAM and parity.…”
Section: Discussionsupporting
confidence: 76%
“…(26) Additionally, we corroborated the findings of previous MR studies that identified a positive causal relationship between AAM and AFB, ALB and age at menopause, and between AFS and ALB. (59)(60)(61) Many estimates identified in the primary analysis appear consistent across sensitivity analyses that aim to account for biases. However, some results did not persist in sensitivity analyses checking for robustness to sample overlap and winner's curse.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, a GRS for adult BMI increasing variants with BMI profiles from early to late adulthood showed that this association was strongest in women with EM (Song et al, 2018). However, (bidirectional) MR analysis did not identify evidence for a causal relationship between ANM and BMI (Day et al, 2015;Ruth et al, 2021;Sarnowski et al, 2018), while a study of Ding et al suggests that there is genetic support for a causal association between higher BMI and earlier ANM (Ding et al, 2020). These contrasting results are likely due to differences in SNP selection and differences in sample size.…”
Section: Obesity and Waist Hip Circumferencementioning
confidence: 97%
“…Observational associations do not indicate causation; however, more recent mendelian analyses suggest causation by linking single nucleotide polymorphisms (SNPs) with risk factors for earlier menopause including earlier age at menarche and lower education level. 21 We will discuss risk factors for POI and early menopause which is divided into the following categories: (1) genetic factors, (2) family history, (3) autoimmunity, (4) early life factors, (5) reproductive factors, (6) lifestyle factors, (7) environmental factors, and (8) iatrogenic factors (summarized in ►Fig. 1 and ►Table 1).…”
Section: Risk Factors For Poi/early Menopausementioning
confidence: 99%